Kebijakan, Sumber Daya, Program dan Kegiatan Perpustakaan - Makmur Syukri; Taufik Hidayat (VISA: Journal of Vision and Ideas, 2023)
The library is the most appropriate place to provide knowledge for studying, reading, conducting research, and also seeking answers to every problem that arises, whether it is a problem that concerns the human individual or problems that exist in society, nation and state. Libraries must be managed with good management so that the library can run well and be enjoyed by visitors who come to the library. Library management ensures that all efforts to achieve library goals utilize human and non-human resources while still paying attention to functions, roles and expertise. Human resources play an important role as organizers and the key to the success of a library. Libraries as information units will have good performance if they are managed with quality human resource management. With good human resource management, library activities will achieve the stated goals.